The Epidemiology of Fatal road traffic Collisions in Trinidad and Tobago, West Indies (2000-2011) - Chavin D. Gopaul; Aruna Singh-Gopaul; Joan M. Sutherland; Luke Rostant; Kristie L. Ebi; Dave D. Chadee (Taylor & Francis Group, 2016)
Summary of what was known• Few studies on road traffic collisions conducted in Latin American and the Caribbean region• Increasing car ownership within the region• Lack of seatbelt usage in Trinidad• Most accidents are associated with alcohol usage• High mortality among pedestriansSummary of what this study adds• Most collisions occur at night• Most collisions occur at weekends• Collisions are evenly distributed throughout the year• More males than females die in fatal collisions• The most productive age group (15-44) is affected the most• More drivers than pedestrians are affected• Reflects the pattern of developed rather than developing countries with respect to time of day for RTCs Background: The purpose of the study is to determine the epidemiology of road traffic collisions (RTCs) in Trinidad and Tobago by characterizing RTCs in terms of number of collisions, fatalities, victim profiles, and locations for the purpose of informing accident prevention programs. Previous studies of RTCs in Trinidad and Tobago were primarily concerned with patterns of drivers use of seat belts, road collisions as a cause of mortality in young men, and the economic burden of road collisions. Attempts were made to model road fatalities, but limited epidemiological data meant that it was difficult to determine trends or develop models. Methods: This study determined the epidemiology of RTCs in Trinidad and Tobago over the period 2000-2011using data collected by the Trinidad and Tobago Road Traffic Branch of the Police Service and secondary data from the Central Statistical Office. Data were analyzed using Excel, SPSS, and R statistical packages. Results: Fatalities were greater among men (80%) than among women (20%) and were highest on two major freeways in Trinidad [the Churchill-Roosevelt Highway and the Sir Solomon Hochoy Highway]. Most collisions occurred during the night among individuals between the ages of 15 and 44 years. Fatalities among drivers steadily increased over the study period and overtook fatalities among pedestrians, who were the group most affected in 2000. Most fatalities occurred at weekends. Conclusions: These patterns can inform (i) education programs and (ii) road and traffic control measures.